UPAYA PERLINDUNGAN HAK ASASI MANUSIA BAGI PEKERJA ANAK DALAM PERSPEKTIF HUKUM POSITIF - Daimanul Hasani Hasani (Fakultas Hukum Universitas Islam Malang, 2022)
ABSTRACTEfforts to protect child labor rights have existed for a long time, both in the form of legislation and in their implementation. However, these efforts have not shown adequate results in accordance with the needs and development of social communities. The role of government and society as well as social organizations that are still lacking in fulfilling the rights of a child, especially in child labor who are still vulnerable to human rights violations, must be seriously considered. The problem of human rights violations in the industrial sector is currently rife in Indonesia related to poverty and underdevelopment. This writing is motivated by the existence of problems, namely, the form of protection of human rights for child labor in a positive legal perspective and the government's efforts to prevent child labor. This research is a type of normative juridical research, using a statutory approach, and a conceptual approach. Sources of legal materials, namely, primary legal materials, secondary legal materials, and tertiary legal materials. The technique of analyzing legal materials is carried out by means of library research and documentation.Keywords: Children, Human Rights, Work.ABSTRAKUsaha perlindungan hak asasi pekerja anak sudah ada sejak lama ada, baik pengaturan dalam bentuk perundang-undangan maupun dalam pelaksanaannya. Namun demikian usaha tersebut belum menunjukan hasil yang memadai sesuai dengan kebutuhan dan pekembangan masyarakat sosial. Peran pemerintah dan masyarakat serta organisasi sosial yang masih kurang dalam pemenuhan hak seorang anak, khsusnya dalam pekerja anak yang masih rentan terhadap pelanggaran hak asasi manusia, harus benar-benar diperhatikan. Permasalahan pelanggaran hak asasi manusia dalam sektor industrial dewasa ini marak terjadi di indonesia berhubungan dengan kemiskinan dan keterbelakangan. Penulisan ini dilatarbelakangi dengan adanya permasalahan yaitu, bentuk perlindungan hak asasi manusia bagi pekerja anak dalam perspektif hukum positif serta, upaya pemerintah dalam mencegah terjadinya pekerja anak. Penelitian ini merupakan jenis penelitian yuridis normatif, dengan menggunakan pendekatan perundang-undangan, dan pendekatan konseptual. Sumber bahan hukum yakni, bahan hukum primer, bahan hukum sekunder, dan bahan hukum tersier. Teknik analisis bahan hukum dilakukan dengan kegiatan studi kepustakaan dan dokumentasi.Kata Kunci: Anak, HAM, Pekerjaan.